Surface coil MR imaging of orbital blowout fractures: a comparison with reformatted CT. - Tonami, H; Nakagawa, T; Ohguchi, M; Takarada, A; Yamamoto, I; Karino, K; Sasaki, K (American Journal of Neuroradiology, 1987)
Four patients with orbital blowout fractures were evaluated by surface coil MR imaging, and the resulting images were compared with computer reformatted CT scans. The surface coil afforded significant improvement in spatial resolution, resulting in better demonstration of the blowout fracture. Surface coil MR was found superior to CT in the assessment of fracture site, extent of prolapsed orbital fat, and muscle entrapment.